Visual basic application for statistical process control: A case of metal frame for actuator production process - Laosiritaworn W. (2017)
Statistical process control (SPC) is one of the important tools in quality control (QC). Commercial software packages are available to implement SPC. However, they are costly and not necessary customize to specific need of each production process. Moreover, they might be difficult for the field operator with limited knowledge of SPC to use the commercial software. In this paper, a visual basic application was developed specifically to meet the demand of a case study company in order to assist the implementation of SPC. The case study company is the manufacturer of metal frame for actuator. The software are able to construct control chart, both x̄ - R chart and x̄ - S chart. These charts are common tools used to determine whether the production process is in control i.e. no assignable causes exist. Moreover, the program is able construct histogram. The software is designed to store process data in SQL database which can be access online. The result indicated that as the program is configured specifically to the process, it can help operator to implement SPC easily even with limited knowledge of SPC.